The hypermobility spectrum in rugby union players, netballers and dancers: implications for injury and performance - Armstrong, Ross (Journal of Education, Health and Sport, 2018)
Objectives: Hypermobility has been associated with injury and performance and a new hypermobility framework has been introduced. This study aimed to report the prevalence of localised joint hypermobility, generalised joint hypermobility (GJH), peripheral joint hypermobility and hypermobility Ehlers-Danlos type in female rugby players, male rugby players, female netball players, female dancers, male and female controls. Methods: This study determined joint hypermobility via the Beighton score and the associated criteria of the hypermobility spectrum in 378 participants. Results: Localised joint hypermobility ranged from 61.11% (netballers), 57.33% (female rugby), 48.15% (male controls), 46.30% (male rugby), 38.33% (female controls) to 28.57% (female dancers). Significant differences existed for Beighton scores (p<0.001) between female dancers and all other cohorts, female rugby and male controls (p=0.005), male rugby and netball (p=0.001), netball and male controls (p=0.001) and female controls and male controls (p=0.021). Prevalence of GJH ranged from 69.84% (female dancers), 25% (netball), 21.67% (female controls), 18.67% (female rugby), 3.70% (male rugby) to 1.85% (male controls). In participants with GJH, dancers had the highest prevalence of pain and dislocation/subluxation. Significant differences existed between dancers and all other groups for hypermobility Ehlers-Danlos type criteria (p<0.001). Five participants met the criteria for diagnosis of hypermobility Ehlers-Danlos type. Male rugby players had the highest prevalence of peripheral joint hypermobility (29.63%). Conclusion: Significant findings between dance and other cohorts may highlight a potential performance adaptation. Significant findings between control groups for the Beighton score may indicate a gender effect. There is a need to consider these factors in relation to performance and injury.